A study of interactive robot architecture through the practical implementation of conversational android - Minato, Takashi; Sakai, Kurima; Uchida, Takahisa; Ishiguro, Hiroshi (Frontiers in Robotics and AI, 2022)
This paper shows the autonomous android robot that can have a natural daily dialogue with humans. The dialogue system for daily dialogue is different from task-oriented dialogue system in that it is not given a clear purpose or necessary information. That is, it needs to generate an utterance in a situation where there is no clear request from humans. Therefore, to continue a dialogue with a consistent content, it is necessary to essentially change the design policy of dialogue management compared with the existing dialogue system. The purpose of our study is to constructively find out the dialogue system architecture for realizing daily dialogue through implementing an autonomous dialogue robot capable of daily natural dialogue. We define the android's desire necessary for daily dialogue and the dialogue management system in which the android changes its internal (mental) states owing to the desire and the partner's behavior and chooses a dialogue topic suitable for the current situation. The developed android was able to continue daily dialogue for about 10 minutes in the scene where the robot and partner met for the first time in the experiment. Moreover, Multimodal Turing Test showed that half of the participants the android was remotely controlled to some degree, that is, the android's behavior is humanlike. This result suggests that the system construction method assumed in this study is an effective approach to realize daily dialogue and the paper discussed the system architecture for daily dialogue.